Sistem Pendidikan Dalam Ayat-Ayat Kisah Maryam dan Nabi Isa a.s. - Raikhan, Raikhan (MADINAH, 2021)
The Qur'an as a miracle of the Prophet Muhammad contains transhistorical values, which means that the Qur'an was revealed in historical reality. This is because the Qur'an came down as a concrete response to history, time periods, certain events, and certain places. While on the other hand, the Qur'an also has a transcendental value, because of which it is eternal, its values are not bound by space and time, it transcends events, by which it is also believed to be eternal. The next main thing is that we cannot understand the Qur'an, both story verses and aqidah verses or even Shari'ah, we separate them. If we understand with an incomplete understanding model then that is an inappropriate or even wrong understanding, atomistic, the purpose of this paper is to understand the Islamic education system through the stories contained in the Qur'an, namely the story of the prophets Isa and Maryam. The effort to understand these verses is to collect related verses and then we arrange these verses according to the life story of the Prophet Isa and his mother, in which there are several important events, then from snippets of events told in the Qur'an the writer seeks to find the educational values contained in it both from the story and from the meaning side. There is something else from the education system, namely the subjects in the story are Prophet Isa, Maryam, and the Children of Israel, the educational material in this story is divided into three, namely Ideological, Historical and Informative, after the material is finished the educational goals are directed at tasks servitude and caliphate, methods include stories and bayan (proof), In the interaction of education even though there are many miracles that show his prophethood, and justify his apostleship, they are al-hawariyyun who are his loyal followers and helpers